2022
DOI: 10.1136/bmjopen-2020-048308
|View full text |Cite
|
Sign up to set email alerts
|

What is the major driver of China’s hospital medical expenditure growth? A decomposing analysis

Abstract: ObjectivesThis study aimed to quantify increases in the medical expenditures of public hospitals associated with changes in service use and prices, which could inform policy efforts to curb the future growth of hospital medical expenditures.DesignNationwide and provincial data regarding service volume, service price and intensity of public hospitals’ outpatient and inpatient care from 2008 to 2018 were extracted from the China Health Statistical Yearbooks, and population size data were obtained from the 2019 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…There is no consensus on whether the rise in health expenses in China is driven by utilization or prices [ 21 ], our research from a macroeconomic perspective complements the evidence that the rise in TMSE in China is associated with the increase in the price levels and inpatient utilization of medical service. Previous studies have confirmed the impact of quantity on medical expenditure [ 3 ]. The focus of this study is to analyze the role of medical service prices in this context.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…There is no consensus on whether the rise in health expenses in China is driven by utilization or prices [ 21 ], our research from a macroeconomic perspective complements the evidence that the rise in TMSE in China is associated with the increase in the price levels and inpatient utilization of medical service. Previous studies have confirmed the impact of quantity on medical expenditure [ 3 ]. The focus of this study is to analyze the role of medical service prices in this context.…”
Section: Discussionmentioning
confidence: 74%
“…The health expenditure is driven by volumes, price or their interplay [ 2 ]. While some studies suggested that utilization is the primary factor accounting for health expenditure [ 3 , 4 ], others contended that prices are the main contributing factor [ 5 , 6 ]. Developed and developing countries have implemented cost containment policies that target price as common strategies to control the rapid growth of health expenditures [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly known that hospital stay is longer in China than in the US for the same procedures, partially due to fee-for-service payment schemes. The total hospital expenditure in China in the inpatient sector is also driven by the service volume effect [ 17 ]. Among the determinants of China’s health expenditure growth, technology was not found to have a significant influencing impact on health expenditure [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Across all of China, average public hospital expenditure per outpatient increased from USD$32 in 2011 to USD$41 in 2018. 17 Similarly, average public hospital expenditure per hospitalization increased from USD$1232 in 2011 to USD$1505 in 2018. 17 Average private hospital expenditure per outpatient and hospitalization is also expected to be lower at the national level relative to Shanghai given that Shanghai is one of China’s wealthiest municipalities.…”
Section: China’s Changing Hospital Landscapementioning
confidence: 99%